2019
DOI: 10.1136/bmjsem-2018-000481
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tetradecyl sulfate versus polidocanol injections for stabilisation of joints that regularly dislocate in an Ehlers-Danlos population

Abstract: ObjectivesTo determine whether there is similarity between tetradecyl sulfate and polidocanol in stabilising a joint from dislocating in patients with Ehlers-Danlos syndrome (EDS).MethodA retrospective analysis of patients with EDS in a sole-practice clinic in New Zealand. Patients must have had the diagnosis of EDS, had easily dislocatable joints, had treatment and at least 3 months’ follow-up. 0.11% tetradecyl sulfate solution, or 0.25% polidocanol solution, was injected to ligament attachments (enthesis) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…0.25% polidocanol was used in joints of the shoulders, hips, knees and the TMJs. [ 30 ] In the present study, we used 1% polidocanol compared to the 3% polidocanol used in venous malformations. The commercially available 3% was diluted to 1% by using sterile water.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…0.25% polidocanol was used in joints of the shoulders, hips, knees and the TMJs. [ 30 ] In the present study, we used 1% polidocanol compared to the 3% polidocanol used in venous malformations. The commercially available 3% was diluted to 1% by using sterile water.…”
Section: Discussionmentioning
confidence: 99%
“…This study was a comparison study between the two agents and did not report the effect of the individual agents. [ 30 ] Therefore, we wanted to assess the effect of 1% polidocanol on isolated TMJ dislocation cases, rather than comparing it to other agents. One study reported successful treatment of hypermobility of TMJ by injecting sclerosing solution into the oblique protuberance and simultaneously cauterising the posterior attachment tissues lateral to the protuberance.…”
Section: Discussionmentioning
confidence: 99%
“…All patients had undergone physical therapy and prolotherapy [ 12 13 ] for craniocervical stabilization prior to OnabotulinumtoxinA injection. The study was exempted by IRB on 3/15/21; all patients were provided with general informed consent per IRB protocol.…”
Section: Methodsmentioning
confidence: 99%